1983
DOI: 10.1002/ijc.2910320118
|View full text |Cite
|
Sign up to set email alerts
|

MHC imbalance and metastatic spread in Lewis lung carcinoma clones

Abstract: Imbalance in the Kb and Db region encoded molecules is observed in Lewis lung carcinoma clones. The uncloned metastatic population and the D122 high-metastatic clone show no expression of H-2Kb products, while the nonmetastatic A9 clone expresses Kb products. Twenty-nine new subclones of 3LL and A9 were analyzed for D-end and K-end membrane expression, primary growth rate and metastatic spread. We show that the imbalance in H-2Kb to H-2Db is correlated with metastatic properties of a given clone, but local tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
2

Year Published

1984
1984
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 21 publications
2
87
2
Order By: Relevance
“…The highly metastatic D122 clone of the C57BL/6-derived Lewis lung carcinoma (Eisenbach et al, 1983) was maintained in DMEM supplemented with 10% heat-inactivated fetal calf serum, glutamine, combined antibiotics, sodium pyruvate and nonessential amino acids. The highly metastatic B16-F10.9 clone of the C57BL/ 6-derived malignant melanoma (Porgador et al, 1989) was grown in DMEM supplemented with 10% heat-inactivated fetal calf serum, glutamine and combined antibiotics.…”
Section: Mice and Cell Culturesmentioning
confidence: 99%
“…The highly metastatic D122 clone of the C57BL/6-derived Lewis lung carcinoma (Eisenbach et al, 1983) was maintained in DMEM supplemented with 10% heat-inactivated fetal calf serum, glutamine, combined antibiotics, sodium pyruvate and nonessential amino acids. The highly metastatic B16-F10.9 clone of the C57BL/ 6-derived malignant melanoma (Porgador et al, 1989) was grown in DMEM supplemented with 10% heat-inactivated fetal calf serum, glutamine and combined antibiotics.…”
Section: Mice and Cell Culturesmentioning
confidence: 99%
“…Four (Benacerraf, 1981;Linsk & Goodenow, 1986;Schwartz, 1982). The class I MHC molecule consists of three alpha regimes, covalently linked to beta-2-microglobulin (beta 2m), which are encoded by separate genes, and linked prior to expression at the cell membrane (Ploegh et al, 1981;Arce-Gomez, 1978 (Eisenbach et al, 1983;1985). Studies on the expression of human MHC class I antigens in primary vs metastatic tumour are limited; for example malignant melanoma, digestive tract, and laryngeal tumours (Ruiz-Cabello et al, 1989;Esteban et al, 1989).…”
mentioning
confidence: 99%
“…With these immunogenic tumours, those with a high level of MHC antigen expression show low metastatic ability; transfection and subsequent expression of the H2K gene into otherwise highly metastatic H2K-negative tumour cell variants reduces tumour growth, and prevents metastasis (Eisenbach et al, 1983;1985). Studies on the expression of human MHC class I antigens in primary vs metastatic tumour are limited; for example malignant melanoma, digestive tract, and laryngeal tumours (Ruiz-Cabello et al, 1989;Esteban et al, 1989).…”
mentioning
confidence: 99%
“…In the 3LL system, we have also reported that reduced expression of MHC class I antigens on the cell surface correlates with reduced immunogenicity and increased malignancy of tumor clones (Eisenbach et al, 1983). The low metastatic clone A9, however, does express signi®cant levels of MHC class I molecules and is highly immunogenic, i.e.…”
Section: Discussionmentioning
confidence: 94%
“…We have isolated, by limiting dilution, high-and lowmetastatic clones from the parental 3LL murine tumor; the high-metastatic clones metastasize exclusively to the lungs (DeBaetselier et al, 1980;Eisenbach et al, 1983). An earlier report of ours showed that the PDGFa receptor is preferentially expressed in high-metastatic but not in low-metastatic 3LL clones (Do et al, 1992).…”
Section: Introductionmentioning
confidence: 99%